Reproductive health service use and associated factors among youths in Becho district, southwest Ethiopia - Teshome Tolosa Waga; Muluneh Shuremu; Asrat Zewdie; Abeza Mitiku Kera; Gutama Haile Degefa (Frontiers Media S.A., 2023)
BackgroundYoung people are less informed, less experienced, and less at ease when it comes to accessing reproductive health services than adults. Though youth-friendly services are designed to accommodate the unique needs of youth, in developing countries like Ethiopia, studies on the level of utilization of reproductive health services are limited.ObjectivesThis study determined the level of reproductive health (RH) service use and associated factors among youths.MethodsA community-based cross-sectional study was conducted in Becho district, Illubabor zone, southwest Ethiopia. A multistage random sampling technique was used to select 702 youths, regardless of their marital status. A pre-tested interviewer-administered questionnaire was used to collect data. The questionnaire includes questions on socio-demographic characteristics, sexual and reproductive health characteristics, knowledge, and components of RH assessment. The data was entered into Epidata version 3.1 and analyzed using SPSS version 22. Multivariable binary logistic regression analysis was used to identify factors associated with the utilization of reproductive health services at a p < 0.05.ResultsA total of 647 youths participated in the study, constituting a response rate of 92.1%. Male youths made up 51.5% of the respondents, with an average (±SD) age of 19.38 (±2.69) years. Reproductive health (RH) services were utilized by 43.9% of youths. Knowledge of RH services (AOR = 4.11; 95% CI: 2.77, 6.09), discussion with family (AOR = 2.18; 95% CI: 1.38, 3.45), history of sexual exposure (AOR = 2.94; 95% CI: 1.95, 4.43), shorter distance from a health facility (AOR = 2.42; 95% CI: 1.63, 3.57), and history of reproductive health problems (AOR = 2.4; 95% CI: 1.34, 4.31) were associated with RH service utilization.ConclusionThe use of reproductive health services among youths is found to be low. Knowledge about reproductive health services, discussion with parents, sexual exposure, distance, and previous experience with reproductive health problems shaped the utilization of RH services by youth. Improving knowledge through information dissemination, creating awareness to increase parent-child intimacy, and expanding health services should be emphasized.